Menjalankan Bisnis Menggunakan Ponsel Pintar Berrupa E-Commerce pada Platform Shopee Didumai - Muhammad Alfi Syahrin Khairi; Edy Prabowo; Putri Damayanti; Zakiah Putri Nurlis; Hendra Syah Putra; Rindu Permata Rahman; Amir Alfath; Titin Indriyani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In the digital era, e-commerce has become an effective solution to increase revenue by using smartphones as the main operational tool. This article aims to analyze the implementation of doing business through the Shopee e-commerce platform in Dumai, especially for Micro, Small, and Medium Enterprises (MSMEs). By adopting a qualitative descriptive approach, data was collected through interviews and literature reviews on digital marketing strategies, challenges, and business opportunities on the Shopee platform. The results show that Shopee provides a number of superior features such as free shipping, coupons, and live streaming that make it easier for MSMEs to promote their products. However, challenges such as limited capital, logistics problems, and tight competition are still the main obstacles. This articl recommends increasing the use of Shopee features by MSMEs with an emphasis on developing quality products and optimizing marketing strategies such as SEO and social media. Shopee’s support through training and more affordable logistics solutions are also considered important in strengthening the competitiveness of MSMEs in the digital market.